2016
DOI: 10.1097/md.0000000000003283
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Rhegmatogenous Retinal Complications in Macular Surgery After Prophylactic Preoperative Laser Retinopexy

Abstract: The aim of the study is to evaluate the clinical characteristics of intraoperative retinal breaks (RBs) and postoperative retinal detachment (RRD) in patients undergoing pars plana vitrectomy (PPV) for macular disorders, who were treated preoperatively with prophylactic peripheral laser retinopexy.This observational cohort study comprised of 254 patients who underwent macular surgery and were preoperatively subjected to prophylactic laser retinopexy anterior to the equator. The main outcome measures were the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…However, the retinal detachment rate after silicone oil removal in the pattern LRP group was similar to those reported in patients who had received intraoperative 360-degree laser retinopexy [4, 9]. …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the retinal detachment rate after silicone oil removal in the pattern LRP group was similar to those reported in patients who had received intraoperative 360-degree laser retinopexy [4, 9]. …”
Section: Discussionsupporting
confidence: 77%
“…The use of intraoperative 360°-LRP technique may be additionally limited by cases of vitrectomy-related failures and complications, when it is not possible to achieve a complete retinal reattachment intraoperatively. Therefore, when used before the surgical procedure [9] or postponed completely for some time after this procedure, 360°-LRP may provide some advantages over intraoperative 360°-LRP. Moreover, 360°-LRP sometimes cannot be performed (in required cases) during the scleral buckling due to failure to achieve complete retinal reattachment caused by residual subretinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…PPLR prior to vitrectomy for vitreoretinal interface disorders has been performed at our tertiary referral center, in an attempt to reduce the incidence of postoperative detachment. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Prophylactic peripheral laser retinopexy (PPLR) prior to PPV for vitreoretinal interface disorders has been performed at our tertiary referral center in an attempt to reduce the incidence of postoperative detachment. 17,18 Following analysis of this series of patients, we observed that PPLR treatment appeared to modify the anatomy of the MH with complete resolution of some holes. Hence, we decided to evaluate changes in the vitreomacular anatomy of MH patients in the time frame-lasting between 20 and 30 days-between the initial visit (PPLR time) and the second visit preceding surgery, comparing patients treated with PPLR at the initial visit to those not treated with PPLR.…”
Section: Introductionmentioning
confidence: 87%
“…Недостатками интраоперационной 360°-ЛРП являются увеличение общего времени операции, необходимость склеропрессии для коагуляции труднодоступных периферических (верхних) участков и часто невозможность завершить ЛРП в полном объеме из-за неполного прилегания сетчатки (из-за наличия остаточной субретинальной жидкости). В связи этим ЛРП может быть выполнена до оперативного вмешательства [9] или перенесена на послеоперационный период.…”
Section: Ophthalmology In Russia 2019;16(3):296-303 введениеunclassified